Changes in tropical Atlantic surface-water environments inferred from late Albian planktic foraminiferal assemblages (ODP Site 1258, Demerara Rise) - Friedrich, Oliver; Bornemann, André; Norris, Richard D.; Erbacher, Jochen; Fiebig, Jens (Cretaceous research, 2017)
Abundance patterns of planktic and benthic foraminifera from the middle to upper Albian of tropical Atlantic Ocean Drilling Program Site 1258 (Demerara Rise) display a pronounced shift between two clearly distinguishable assemblages: (1) a foraminiferal fauna dominated by coiled taxa, which is inferred to represent a deep and/or weak oxygen minimum zone, and (2) abundant clavate and biserial taxa, inferred to record a shallow and/or strong oxygen minimum zone at Demerara Rise. The entire sequence is rich in organic matter (3-6 wt% TOC) of a marine phytoplankton origin (δ13C ∼ −28‰), consistent with a highly productive region. Both the high productivity and changes in foraminiferal assemblages are consistent with changes in the mean latitudinal position of the Intertropical Convergence Zone (ITCZ) over the South American continent. Movements of the ITCZ are proposed to reduce the amount of runoff during the 'clavate-dominated' cycles, leading to the intensification of upwelling and therefore a stronger oxygen minimum zone compared to the intervals dominated by coiled foraminifera. We have previously found a similar hydrographic cycle in Turonian to Coniacian sections from the same area suggesting that this climate cyclicity and palaeogeography was long-lived off NE South America (∼15 million years). Due to the stratigraphic position of the interval with high abundances of clavate planktic foraminifera and the inferred strong oxygen minimum zone, it is tentatively proposed that this interval represents a local expression of the OAE 1c event within the long-living Demerara Rise upwelling system.